Outcomes of Endoscopic and Surgical Pancreatic Necrosectomy: A Single Institution Experience. Issue 9 (September 2019) - Martinez, Manuel; Cole, Joshua; Dove, James; Blansfield, Joseph; Shabahang, Mohsen; Wild, Jeffrey; Widom, Kenneth; Torres, Denise; Factor, Matthew
Pancreatic necrosis can be managed conservatively; however, infection of pancreatic necrosis usually dictates more aggressive management. Our study aimed to assess the outcomes of open pancreatic necrosectomy (OPN) and endoscopic pancreatic necrosectomy (EPN) in a single center. Data from patients undergoing pancreatic necrosectomy at the Geisinger Medical Center from January 1, 2007, to April 25, 2016, were collected and retrospectively analyzed. Cohorts were composed of EPN (n = 22) and OPN (n = 34) groups. The prevalence of preoperative respiratory failure, septic shock, and multiorgan dysfunction syndrome was higher in the OPN group. The OPN group presented with a higher Bedside Index Severity in Acute Pancreatitis score. Postoperative abscess, persistent kidney dysfunction, and death were more frequent in the OPN group. The EPN group had a higher read-mission rate. The results of the univariate analysis for complication and mortality demonstrated that higher mortality and persistent kidney dysfunction were associated with the procedure type, specifically OPN and with a higher Bedside Index Severity in Acute Pancreatitis score. Patients who presented with higher severity of disease underwent an OPN, whereas EPN often was performed successfully in a more benign clinical setting. However, patients with infected necrosis are served best in a tertiary medical facility where multiple treatment modalities are available.